PSYCHORELIGIOUS DIMENSIONS ON THERAPY PERSPECTIVE IN THE MIDDLE OF THE COVID-19 PANDEMIC - Sarnoto, Ahmad Zain; Rahmawati, Sri Tuti; Hamzah, Naemah Binti (Psikis : Jurnal Psikologi Islami, 2022)
This paper examines the psychoreligious dimensions in a therapy perspective, which can be performed on people affected and those who are not affected by the 2019 corona virus (Covid-19), because pandemic situations often cause social chaos, and are often even discovered from religious thought and the socio-religious community. The kind of research in this paper is library research, using a qualitative-philosophical approach. The data were analyzed by using the Religious Cognitive Emotional Theory (RCET). This study found; first, physical healing efforts require realistic religious thinking to explain that the purpose and meaning of their life is very important, and keeping the body healthy is the most important teaching of religion. Second, the therapy process can be carried out by the therapists by directing clients into three main dimensions: psycho-religious, cognitive-religious, and spiritual-religious. The findings in this study contribute to increasing the treasures of thought in therapy disciplines in the midst of the Covid-19 pandemic.